2021
DOI: 10.1186/s12245-021-00357-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting emergency department visits in a large teaching hospital

Abstract: Background Emergency department (ED) visits show a high volatility over time. Therefore, EDs are likely to be crowded at peak-volume moments. ED crowding is a widely reported problem with negative consequences for patients as well as staff. Previous studies on the predictive value of weather variables on ED visits show conflicting results. Also, no such studies were performed in the Netherlands. Therefore, we evaluated prediction models for the number of ED visits in our large the Netherlands t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…The overall number of ED visits was dramatically decreased in this pandemic period compared to a seasonally comparative period in the prior year. The 14% relative increase in the proportion of weekday visits on Mondays that we reported during the 2019 comparative period, relative to other weekdays (i.e., Tuesday through Friday), was comparable to the 12% to 17% relative increases reported in other ED studies [ 8 10 ]. We are unaware of any other ED studies that have reported this disappearance of the historical Monday effect associated with a pandemic lockdown period.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The overall number of ED visits was dramatically decreased in this pandemic period compared to a seasonally comparative period in the prior year. The 14% relative increase in the proportion of weekday visits on Mondays that we reported during the 2019 comparative period, relative to other weekdays (i.e., Tuesday through Friday), was comparable to the 12% to 17% relative increases reported in other ED studies [ 8 10 ]. We are unaware of any other ED studies that have reported this disappearance of the historical Monday effect associated with a pandemic lockdown period.…”
Section: Discussionsupporting
confidence: 84%
“…Higher volumes of ED patients have been historically been reported to occur on Mondays [8][9][10]. Given this trend, we have historically scheduled additional physician and nurse staffing coverage on Mondays to manage the workload.…”
Section: Introductionmentioning
confidence: 99%
“…The 14% relative increase in the proportion of weekday visits on Mondays that we reported during the 2019 comparative period, relative to other weekdays (i.e., Tuesday through Friday), was comparable to the 12% to 17% relative increases reported in other ED studies. 810 We are unaware of any other ED studies that have reported this disappearance of the historical Monday effect associated with a pandemic lockdown period. One United Kingdom database study has reported that there is no longer an increase in the number of ED fracture visits presenting on weekends during the pandemic period as compared to a pre-pandemic period.…”
Section: Discussionmentioning
confidence: 98%
“…Higher volumes of ED patients have been historically been reported to occur on Mondays. [8][9][10] Given this trend, we have historically scheduled additional physician and nurse staffing coverage on Mondays to manage the workload. This study aims to characterize the weekday variability in patient volume in a U.S. pediatric emergency department during a pandemic period and a comparative pre-pandemic period.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically in the EDs of Antoniushove, ARMA, Davis, Joon, PM, RG, and Westeinde hospitals, it was observed that the FE variables index.num, yday and week displayed high levels of importance (Table A5), surpassing those attributed to metereological variables, which are typically considered informative in predicting patient arrivals in EDs; e.g., [3], [6], [7], [38], [42], [52]. The systematic review by Wangon et al [39] concluded that calendar variables hold greater importance than meteorological variables in predicting patient arrivals in EDs, aligning with our findings.…”
Section: Discussionmentioning
confidence: 98%